Physicochemical and stability of organic rice bran milk added with hydrocolloids - Issara, Utthapon; Rawdkuen, Saroat (Food and Applied Bioscience Journal, 2017)
The present work was aimed to study the effect of four hydrocolloids on physicochemical and stability of organic rice bran milk (RBM) during refrigerated storage. Guar gum (GUA), xanthan gum (XAN), pectin (PEC), and carrageenan (CAR) at the concentrations of 0, 0.05, 0.1, 0.3 and 0.5% (w/v) were gradually added into the pasteurized RBM before their properties and stability determinations. The results showed that GUA, XAN, and PEC were the most effective substances for pH reduction, while CAR increased the pH of RBM (p<0.05). Total soluble solid (TSS) of RBM added with different hydrocolloids was ranged from 4.3±0.71 to 6.3±0.71°Brix. The viscosity of RBM after 7 days storage at 4°C was 4.05±0.04 to 229.77±1.48 cP, which significantly higher than the control (3.05±0.01cP) (p<0.05). The highest stability of RBM was found when XAN at the level >0.3 (w/v) was applied. According to the results, GUA at all concentrations seem to be the most effective hydrocolloid for physicochemical properties improvement, while XAN was provided the good product stability.